Single-Machine Group Scheduling Problems with Deterioration to Minimize the Sum of Completion Times - Yong He (Mathematical Problems in Engineering, 2012)
We consider two single-machine group scheduling problems with deteriorating group setup and job processing times. That is, the job processing times and group setup times are linearly increasing (or decreasing) functions of their starting times. Jobs in each group have the same deteriorating rate. The objective of scheduling problems is to minimize the sum of completion times. We show that the sum of completion times minimization problems remains polynomially solvable under the agreeable conditions.